A very limited role of tropospheric chlorine as a sink of the greenhouse gas methane - Gromov, Sergey; Brenninkmeijer, Carl A. M.; Jöckel, Patrick (Atmospheric Chemistry and Physics, 2018)
Unexpectedly large seasonal phase differences between CH4 concentration and its 13C∕12C isotopic ratio and their inter-annual variations observed in southern hemispheric time series have been attributed to the Cl+CH4 reaction, in which 13CH4 is discriminated strongly compared to OH+CH4, and have provided the only (indirect) evidence of a hemispheric-scale presence of oxidative cycle-relevant quantities of tropospheric atomic Cl. Our analysis of concurrent New Zealand and Antarctic time series of CH4 and CO mixing and isotope ratios shows that a corresponding 13C∕12C variability is absent in CO. Using the AC-GCM EMAC model and isotopic mass balancing for comparing the periods of presumably high and low Cl, it is shown that variations in extra-tropical Southern Hemisphere Cl cannot have exceeded 0.9 × 103atomscm−3. It is demonstrated that the 13C∕12C ratio of CO is a sensitive indicator for the isotopic composition of reacted CH4 and therefore for its sources. Despite ambiguities about the yield of CO from CH4 oxidation (with this yield being an important factor in the budget of CO) and uncertainties about the isotopic composition of sources of CO (in particular biomass burning), the contribution of Cl to the removal of CH4 in the troposphere is probably much lower than currently assumed.